INSURABLE INTEREST IN PROPERTY INSURANCE LAW: Policy and History - Dumais, Daniel (Revue de droit de l'Université de Sherbrooke)

(untitled) (Revue de Droit de l’Université de Sherbrooke, 1988)
The definition of insurable interest has been recently modified by the Supreme Court of Canada. Indeed, in the case of Constitution Insurance Co. of Canada c. Kosmopoulos, the Court has drastically and deeply reviewed and reformed this rule. This article is aimed at establishing the correctness of this decision. To this end, the author examines the policy and the history of this principle. This will allow the reader to better understand and appreciate the importance of this evolution in the area of insurance.